(untitled) (Innovaciones Educativas, 2025)
A Learning Ecology (LE) was implemented through the Moodle platform as a complement to in-person classes in a General Chemistry course taught at the Sede Interuniversitaria de Alajuela (SIA) of the University of Costa Rica (UCR). The objective of this study is to analyze student interaction with and experiences in the learning ecology. Specifically, the study aims to identify aspects related to connectivity, internet access, types of technological devices used, as well as the accessibility and frequency of use of the LE. Additionally, it seeks to characterize the ecology based on students’ shared experiences. The study adopted a mixed-methods approach using a concurrent nested design with a dominant model (DIAC). All students enrolled in the course during the first academic term of 2023 from the Industrial Engineering and Mechanical Engineering with an emphasis in Fire Protection (SPI) programs were invited to participate. A total of 60 students took part in the study. Students perceived the LE as a valuable, flexible, and effective resource for supporting their academic tasks. Features such as accessibility and the variety of virtual resources available encouraged self-paced learning, supported individual academic needs, and granted students greater control over their educational process. The findings show that integrating virtual resources enriches the learning experience and enhances interaction among participants, allowing for a more personalized educational process. The use of the LE as a supplement to in-person classes proved beneficial, promoting adaptive, studentcentered learning. It is recommended that university instructors consider integrating such virtual components into their courses to enrich the educational experience.